FISCAL AUTONOMY IN THE REVENUE COLLECTION OF LOCAL ADMINISTRATIVE ORGANIZATIONS: A CASE STUDY OF CITY MUNICIPALITIES - Wiraphanphong, Airawee; Thomrongajariyakul , Jinda (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2025)
The aims of this research were: (1) to measure the fiscal autonomy in the revenue of city municipalities during the fiscal years 2018–2022, (2) to explore the trends in fiscal autonomy in revenue among city municipalities over the same period, and (3) to propose policy recommendations to enhance local fiscal autonomy in revenue. The study employed a quantitative research approach, utilizing indices such as the Revenue Independence Index (RII), the Revenue Dependency IndexGovernment (RDIG), and the Revenue Dependency IndexSubsidy (RDIS). The results of the study were as follows. (1) The fiscal autonomy of the municipalities in terms of revenue during the fiscal years 2018–2022 was at a very low level, with the RII index at an average of 15.60%, reflecting that the municipalities still had no fiscal autonomy in terms of revenue, while the RDIG index was at a medium level, with an average of 43.67%, and the RDIS index was also at a medium level, with an average of 40.75%, reflecting that the municipalities needed to continue to rely on fiscal revenue collected and allocated by the government as well as subsidies. (2) The fiscal autonomy of municipalities tended to decrease in the fiscal years 2020–2021 due to the COVID-19 pandemic, amendments to laws, and Cabinet resolutions affecting local revenue collection. In fiscal year 2022, the trend of independence increased but was not as high as that in the fiscal years 2018–2019. (3) To enhance fiscal autonomy in terms of revenue, the government should improve tax regulations, reduce local control and decentralize fiscal power, while municipalities should develop new revenue streams, innovations and revenue collection channels.